Automotive underbody diffuser for battery thermal management. (2015) - Khasow, Rocky; Agelin-Chaab, Martin
This paper investigates underbody aero-thermal management of a hypothetical battery pack. Underbody diffusers are specifically designed to channel air for cooling a surface of the battery pack without significantly increasing aerodynamic drag. Numerical simulations are conducted to study the cooling and drag effects of the new diffusers on the battery pack. The numerical results show that the temperature of the battery pack upstream decreased whereas that at the downstream slightly increased compared to the no diffuser case, in addition to having a larger range of temperatures. There are smaller hot spots in comparison to the no diffuser case, which limit the number of cells in a battery that would be affected by the temperature increase, thus preventing damage. With further studies and improved diffuser design, the present work has the potential to offer better alternative locations for installing EV and HEV battery packs for improved air cooling.